If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(z + -2) + -3z = 44 Reorder the terms: 7(-2 + z) + -3z = 44 (-2 * 7 + z * 7) + -3z = 44 (-14 + 7z) + -3z = 44 Combine like terms: 7z + -3z = 4z -14 + 4z = 44 Solving -14 + 4z = 44 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 4z = 44 + 14 Combine like terms: -14 + 14 = 0 0 + 4z = 44 + 14 4z = 44 + 14 Combine like terms: 44 + 14 = 58 4z = 58 Divide each side by '4'. z = 14.5 Simplifying z = 14.5
| x-8=0.64 | | -5+2x=13 | | 7x+4=10y-7 | | 100+1x=5x-1x | | -6x^2-35x-33=0 | | 50=8+2a | | -26=5y-6 | | 6x^2+35x+33=0 | | 8x+47=8[x+5] | | 12x-18=15x | | 6x^2-35x-33=0 | | 100+1x=5x-1 | | -3i/7=-7/8 | | (5y^3-2y^2)(-35y+14)=0 | | 2(5x+7)=24 | | 6f+10=2f-30 | | 18-7f=-9 | | 10x+600=664 | | 7x/8=-10 | | 14b=16b+8 | | X-(-16)=16 | | (8X-5)-(3X-3)=0 | | 48=16s | | -5x-9=-24 | | 1=w-4 | | 6c+4=c+24 | | -5l/9=25 | | 5x+7=-33 | | x^4-6x^2-2=0 | | 45+1.99m=68.88 | | 7p+4=-2+p | | 2W^2+11w+5=0 |